Exploring the Need for “Omah Baskara” a Local Wisdom-Based Learning Media for Teaching East Java’s Cultural Diversity - Rizki Farista Sari; Kharisma Eka Putri; Sulistiono Sulistiono (Actual Insight, 2026)
Learning activities in Natural and Social Sciences at the elementary school level still make limited use of local wisdom-based learning media. Most existing learning media do not incorporate cultural elements from students' surrounding environments, highlighting the need for a needs analysis of local wisdom-based learning media. This study aimed to analyze the need for the